Influence of Multimedia Creative Teaching in Science Subjects on Student Motivation - Ayuni, Fitri; Hadiyati, Putri Octa (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
The use of interactive multimedia is a technological aid in learning that supports learning activities in class, especially in improving academic grades. Using a variety of appropriate media can increase students' motivation when learning. The aim of this research is to determine whether or not there is an influence of creative multimedia teaching in science subjects on the motivation of class IV students at SDIP YLPI Pekanbaru. The type of research used is quast experiment (quasi-experimental research or quasi-experiment) with a non-equivalent group control design. The population in the research here is all class IV students at SDIP YLPI Pekanbaru, totaling 44 students with a total sample of class IV taken using the totaling sampling technique. Data collection techniques in this research used observation, questionnaires and documentation. The data analysis methods applied in this research are descriptive statistical analysis and inferential statistical analysis. Based on the research results, it can be concluded that the Sig. (2-tailed) is <0.001 <0.05, so it can be concluded that there is an influence of creative multimedia teaching in science subjects on the motivation of class IV students at SDIP YLPI Pekanbaru.